Cryogenic liquid nitrogen stimulation-induced cracking in gas-enriched shale reservoirs: A numerical investigation. (14th April 2023) - Han, Songcai; Gao, Qi; Yang, Junchao; Wang, Lei; Cheng, Yuanfang; Yan, Chuanliang; Shi, Xian
Highlights: The trans -scale cracking process of the shale reservoir stimulated by LN2 is modeled. The mechanism of cryogenic stimulation-induced multiple fractures is revealed. Fracture initiation pressure and fracture morphology under different factors are analyzed. Preferable candidates for LN2 stimulation in shale reservoirs are recommended. The stimulation effects of three fracturing fluids, LN2, H2 O and S-CO2, are compared. Abstract: Cryogenic shock-induced brittle cracking has promising application prospects in reservoir stimulation. In this paper, a fully coupled thermo-hydro-mechanical (T-H-M) model combined with the statistical meso -damage theory is proposed to investigate the trans -scale progressive cracking process of shale gas reservoirs stimulated by liquid nitrogen (LN2 ). In this theoretical framework, shale meso -heterogeneity in both thermo-mechanical and hydraulic properties is characterized by two independent statistical distribution functions; temperature-dependent rock properties and temperature- and pressure-dependent fluid thermodynamic properties are described using some experimental and theoretical formulas. The numerical model is implemented in a finite element context and subsequently validated against existing classical coupling results. Numerical results demonstrate that LN2 fracturing accompanied by the unique cryogenic shock effect leads to a complex cracking process involving multiple-point fracture initiation, asymmetric macrofracture propagation, and primary fracture bifurcation. Sensitivity analysis indicates that approximately equidistant or equilength radial fractures may be generated at a lower stress difference, lower permeability, or higher elastic modulus; both fracture initiation pressure and induced fracture morphology are more sensitive to injected fluid temperature relative to initial reservoir temperature; a larger thermal expansion coefficient is beneficial for inducing more fractures, but not applicable to the thermal conductivity. Preferable candidates for LN2 stimulation to generate multiple fractures in shale reservoirs are recommended. It is also found that compared with H2 O and supercritical CO2, fracturing using LN2 can generate fractures with lower initiation pressure and greater complexity. Preliminary results confirm the potential of using LN2 fracturing to improve the stimulation effect of shale reservoirs.